Field notes contributed by Philip J. Walsh, summer 1996 - Walsh, Philip J.et al (1996)
List of birds and locations contributed by Philip J. Walsh. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1996. Epson - sheet feed